Three tones to narrate the fiesta: Agustín Yáñez, Juan Rulfo y Juan José Arreola - Alemany Bay, Carmen (Anales de Literatura Hispanoamericana, 2018)
Three narrators from Jalisco, representative of the best Mexican narrative of the fifties and sixties, Agustín Yáñez, Juan Rulfo and Juan José Arreola, tackle the festive subject matter in part of their work. Yáñez will do this in some of the stories of Los sentidos al aire, Rulfo will dwell on an aura of doom of the festive in some scenes of Pedro Páramo, as in some stories of El Llano en llamas, and, lastly, Arreola, in his novel La feria, will resort to Zapotlán festivities to stand out the idiosyncratic as well as the confrontation between the religious and the festive. There is a great number of coincidencies among the texts mentioned, and we will deal with them, but, mainly, we want to stand out the value of the idiosyncratic that converge on their stories to tackle the same topic, the different atmosphere and perspectives as well as narrative strategies. All in all, we want to identify their different rhetorical abilities to get to the bottom the metaphoric value of the festive.
Keywords: Feast; Mexican Narrative; Yáñez; Rulfo; Arreola